Pengaruh Pengetahuan Halal, Citra Merek dan Harga Terhadap Keputusan Pembelian Kosmetik You (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Jambi) - Ema Fitri; Ridhwan Ridhwan; Heni Pratiwi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine and analyze the influence of halal knowledge, brand image, and price on the decision to purchase YOU cosmetics among studentsat the Faculty of Economics and Business, University of Jambi. The research method used is quantitative. The data source used is primary data in the form of a questionnaire using a 1-5 Likert scale with 90 respondents, namely students who use YOU cosmetics at the Faculty of Economics and Business, University of Jambi, actively in 2025. The data analysis technique used is multiple linear regression analysis. Data processing was conducted using SPSS 25 software. The results of this study indicate that the brand image and price variables have a positive and significant influence on the purchase decision of YOU cosmetics among students at the Faculty of Economics and Business, University of Jambi, while the halal knowledge variable at the Faculty of Economics and Business, University of Jambi, while the halal knowledge variable does not influence the decision to purchase YOU cosmetics. YOU Beauty is a local Indonesian cosmetics brand known for offering high-quality beauty products at affordable prices.